2010
DOI: 10.1200/jco.2009.24.2024
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Pertuzumab and Trastuzumab in Patients With Human Epidermal Growth Factor Receptor 2–Positive Metastatic Breast Cancer That Progressed During Prior Trastuzumab Therapy

Abstract: The combination of pertuzumab and trastuzumab is active and well tolerated in patients with metastatic HER2-positive breast cancer who had experienced progression during prior trastuzumab therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
349
2
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 578 publications
(363 citation statements)
references
References 21 publications
5
349
2
7
Order By: Relevance
“…The combination of trastuzumab and pertuzumab has achieved success in the clinic. A phase II trial in patients with Her2-positive metastatic breast cancer who had previously progressed on trastuzumab therapy achieved a 50% clinical benefit rate and 24.2% objective response rate (43). We show here that MM-111 inhibition of ligand-activated ErbB3 phosphorylation is superior to pertuzumab and the combination of MM-111 and trastuzumab is more effective at inhibiting tumor cell growth than pertuzumab plus trastuzumab.…”
Section: Discussionmentioning
confidence: 63%
“…The combination of trastuzumab and pertuzumab has achieved success in the clinic. A phase II trial in patients with Her2-positive metastatic breast cancer who had previously progressed on trastuzumab therapy achieved a 50% clinical benefit rate and 24.2% objective response rate (43). We show here that MM-111 inhibition of ligand-activated ErbB3 phosphorylation is superior to pertuzumab and the combination of MM-111 and trastuzumab is more effective at inhibiting tumor cell growth than pertuzumab plus trastuzumab.…”
Section: Discussionmentioning
confidence: 63%
“…8 Their mechanisms of action are complementary, providing broader blockade of the HER2-positive tumor cell proliferation and survival signaling. 9 The CLEOPATRA clinical trial showed that patients with metastatic HER2-positive breast cancer treated with combination of pertuzumab and trastuzumab plus docetaxel significantly prolonged progression-free survival, 10 and simultaneous blockade of HER2 by trastuzumab and pertuzumab may overcome trastuzumab-resistance. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Pertuzumab is currently undergoing ovarian cancer trials in combination with cytotoxic agents including gemcitabine (20) and carboplatin (21). A recent trial in breast cancer suggests that the combination of trastuzumab and pertuzumab can produce clinical benefit in 50% of trastuzumab-resistant disease (22), despite pertuzumab having very limited activity as a single agent. The modest single-agent response rate of pertuzumab was reported for breast cancer patients whose tumors did not overexpress HER2 (23).…”
Section: Introductionmentioning
confidence: 99%